(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper focuses on legal interpretation as an aspect of legal doctrine. On the basis of some semantical assumptions founded on Wittgenstein’s views on meaning, Ideal with the interpretation as an exception to the standard understanding of language, stating that one interprets a legal provision if its meaning in a concrete situationis pragmatically uncertain, seeking to suggest a meaning among a range of possibilities. I also put forward a directive of interpretation based on the contextual probabilityof the meaning suggested (in terms of acceptability by the involved audience)and re-examine customary issues such as analogical and teleological arguments.